(untitled) (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2022)
Introduction: Nutritional status is an important factor affecting mental health and the development of psychiatric disorders. However, there are quite limited research on nutritional status and mental health and there are a variety of results from these epidemiological studies. Aim: This study aimed to find out overview of nutritional status and the insidence of common mental disorders in nutrition students at Public Health Faculty of Hasanuddin University. Methods: The study was conducted toward 165 nutrition students at Public Health Faculty of Hasanuddin University. Data were collected via online using questionnaire with the help of Google Form application. Nutritional status is determined based on BMI and BMI-for-age indicators calculated from respondent’s weight and height data. The measurement of common mental disorders was carried out using the Depression, Anxiety, Stress Scales (DASS-42) questionnaire. Furthermore, descriptive analysis was carried out using the SPSS 22 program. Results: Nutrition students at Public Health Faculty of Hasanuddin University generally have good/normal nutritional status (66,4%). More students experienced common mental disorders (77,0%). Based on the nutritional status, respondents who experienced common mental disorders were most in the group of malnutrition/very thin (100%) and obese respondents (100%). Similar results were obtained in the gourp of anxious respondents. Meanwhile, most of depressed respondents were in the obese group (50%). Conclusion: Nutrition students at Public Health Facultyof Hasanuddin University who experienced common mental disorders tend to have malnutrition/very thin and obesity nutritional status. Further research is required to understand the association of nutritional status and the incidence of common mental disorders.